Deletion in KARLN intron 5 and predictive relationship with bovine tuberculosis and brucellosis infection phenotype - Rossi, Ursula Amaranta; Caffaro, María Eugenia; Raschia, Maria Agustina; Hasenauer, Flavia Carolina; Poli, Mario Andres; Rossetti, Carlos Alberto (Springer, 2023)
Kalirin (gene: KALRN) is a Rho-GEF kinase linked to neurodegenerative diseases in humans. Unexpectedly, various polymorphisms in KALRN gene were previously associated with resistance to bacterial infections in ruminants. In this study, we evaluated the effect of the rs384223075 (RS-075) deletion in KALRN intron 5 on the occurrence of Mycobacterium bovis and Brucella abortus infections in cattle. We performed two separate case-control association analyses: one for bovine tuberculosis (bTB) using 308 Holstein and Jersey cows from three herds with prevalence between 5 and 15% for this infection; and another for brucellosis using 140 Holstein and beef crossbred cows from two herds with high prevalence for brucellosis (> 30%). In the bTB analysis, the RS-075 deletion frequency was higher among cases than controls (p = 0.0001), and the absence of the RS-075 deletion allele was associated with negative PPD-skin test results (p = 0.0009) at genotype level. On the contrary, RS-075 was not associated with Brucella spp. serological status (p = 0.72) but, unexpectedly, the deletion allele was more frequent among controls than cases in the beef crossbred herd (0.31 vs. 0.14, p = 0.02). In concordance with this observation, in vitro assays showed that the RS-075 deletion could be linked to an enhanced cellular response to bacterial antigens and unspecific stimulation in mononuclear cells derived from beef crossbred cows, specifically the reactive nitrogen species production (p = 0.008) and proliferation capacity (p = 0.018). This study is consistent with other reports that support an important role of the KALRN gene and its polymorphisms in the host response to intracellular pathogens.